Stranger danger awareness in Williams syndrome. (29th May 2013) - Riby, D. M.; Kirk, H.; Hanley, M.; Riby, L. M.
Abstract Background The developmental disorder Williams syndrome (WS) is characterised by a distinctive cognitive profile and an intriguing social phenotype. Individuals with the disorder are often highly social engaging with familiar and unfamiliar people and once in an interaction they often show subtle abnormalities of social behaviour. Atypically increased approach to unfamiliar people is widely reported in the existing literature for both children and adults. Parents frequently report interactions with unfamiliar people as a major concern. Methods In this study we aimed to evaluate 'stranger danger' awareness using a video vignette task with individuals who had WS. When linked to other components of the WS phenotype (e.g. reduced intellectual ability, increased social approach) an awareness of stranger danger is particularly important. Results Qualitative and quantitative data showed that young people with WS have difficulties making judgements about whether or not to trust and engage in conversation with unfamiliar people. Qualitative data showed that individuals with WS often suggested that they would engage in an interaction with an unfamiliar person. Conclusions The findings have substantial implications for the safety of young people with the disorder and emphasise the need for intervention regarding this behaviour.